Effects of fatigue on kinematics and kinetics during overground running: a systematic review - Winter, S.; Gordon. S.; Watt, K. (The Journal of Sports Medicine and Physical Fitness, 2017)
INTRODUCTION: Understanding kinematic and kinetic changes with fatigue during running is important to assess changes that may influence performance and injury. The aim of this systematic review was to identify, critique and summarize literature about the effects of fatigue on kinematics and kinetics during a fatiguing overground run and present the reported influence on performance and injury.